Structural, Electronic and Mechanical Properties of Few-layer Porous Nanosheet from Spheroidal Cage-like ZnO Polymorph - Hong Lien, Le Thi; Thi Thao, Nguyen; Tuoc, Vu Ngoc (VNU Journal of Science: Mathematics - Physics; Vol 36 No 4DO - 10.25073/2588-1124/vnumap.4517, 2020)
The low-dimensional II-VI group semiconductors have recently emerged as interesting candidate materials for the tailoring of two dimensional (2D) layered structures. Herein, a series of the cage-like nanoporous composed of spheroidal hollow cages (ZnO) 12 , cutting from the high symmetrical cubic SOD cage-like polymorph as building block, is proposed. We have performed the density-functional tight binding (DFTB+) calculations on the structural, electronic and mechanical properties of this few-layer SOD-cage-block nanosheet series, to investigate the effects of structural modification and sheet thickness on their structural, electronic, and mechanical properties. Optimized geometries, formation energy, phonon spectra, electronic band structure, and elastic tensor calculation has ensured the energetically, dynamical and mechanical stability for the sheets. Furthermore, the theoretically found nanosheet series possess an intrinsic wide direct band gap preserving from wurtzite tetragonal-based bonding. This high symmetry wide bandgap semiconductor nanosheet series and their derivatives are expected to have broad applications in photocatalysis, and biomedicine.